2007
DOI: 10.1016/j.ijgo.2007.05.049
|View full text |Cite
|
Sign up to set email alerts
|

Sexual abuse experienced by married Egyptian women

Abstract: The study's findings demonstrate an immediate need for the prevention of SA in Lower Egypt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
0
7
1
2
Order By: Relevance
“…This implies that young boys have learned in schools and from friends about sexuality and the harmful effect of FGC on sexuality. It is known, from the literature, that many women with FGC suffer trouble with desire, arousability, satisfaction, and ability to achieve orgasm in the general population [31, 32]. Thus it is not surprising that women with FGC would have problems with sexual intercourse.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that young boys have learned in schools and from friends about sexuality and the harmful effect of FGC on sexuality. It is known, from the literature, that many women with FGC suffer trouble with desire, arousability, satisfaction, and ability to achieve orgasm in the general population [31, 32]. Thus it is not surprising that women with FGC would have problems with sexual intercourse.…”
Section: Discussionmentioning
confidence: 99%
“…Although marital rape is not recognized in the Arab region as a crime, sexual violence has a profound impact on the woman's health especially if the woman feels trapped (Elnashar, Ibrahim, Eldesoky, Aly, & Hassan, 2007). A study in Bangladesh found that 27% of women accepted marital rape (Selic, Pesjak, & Kersnik, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…ABD'de yapılan çalışmalarda ise bu oranın % 7,7 ile % 23,1 arasında değiştiği bildirilmiştir (18)(19)(20). İngiltere'de yapılan bir çalışmada evlilik içi cinsel saldırı oranının % 13 olduğu bildirilmiştir (21) Mısır'da eşleri tarafından cinsel saldırıya uğrayan 936 olgunun değerlendirildiği bir çalışmada olguların % 93,6'sının haftada 2 ile 4 defa cinsel saldırıya uğradığı bildirilmiştir (22). Tunus'ta 197 evli kadınla ile ilgili yapılan bir çalışmada evli kadınların % 10,6'sının evlilik içi cinsel saldırıya maruz kaldığı belirlenmiştir (23).…”
Section: Discussionunclassified
“…Literatürde, evlilik içi cinsel saldırı için, küçük yaşta evliliklerin, eğitim seviyesinin düşük olmasının önemli risk faktörleri olduğunu göstermektedir (12)(13)(14)(15)(16)22,23,25). Çalışmamızda literatür ile uyumlu olarak, olguların % 48,2'sinin 17-24 yaş grubunda oldukları, cinsel saldırının genellikle evlilik ile başladığı anlaşılmaktadır.…”
Section: Discussionunclassified